Adapting the Copenhagen Burnout Inventory (CBI) Instrument for Elementary School Teachers Working with Gifted Students : Adaptasi Alat Ukur Copenhagen Burnout Inventory (CBI) untuk Guru SD yang Bekerja dengan Siswa Berbakat - Ludwina, Gretta; Lubis, Fitriani Yustikasari (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2023)
The burnout phenomenon is prevalent in the teaching profession, and it significantly impacts teachers’ ability to cater to the unique needs of gifted students. Such burnout led to undesirable consequences for both teachers and students alike. A reliable instrument capable of measuring teachers’ burnout concerning gifted students’ education is necessary. The Copenhagen Burnout Inventory (CBI) is a suitable instrument for measuring burnout. It specifically focuses on pure exhaustion rather than considering burnout as a syndrome. However, this instrument has not yet been adapted to the Indonesian language. This study aimed to validate and determine the reliability of the Indonesian adaptation of the CBI. Content Validity Index (CVI) was utilized to assess the instrument’s validity, while Classical Test Theory (CTT) was employed to evaluate the reliability. A total of 76 elementary school teachers with experience in teaching gifted students were included in the research. The results showed that the adaptation of the instrument was valid and effectively measured relevant constructs related to burnout. The instrument exhibited a very high level of reliability, indicating strong dependability. Subsequent discussions should explore suggested adjustments for this adaptation, drawing insights from CTT findings.